Answer:b
Step-by-step explanation:
Answer:
x = 42.5
Step-by-step explanation:
It is said:
If two angles are not corresponding, then they make up 180°. They are more known as supplementary angles.
So the equation is:
a + b = 180°
Substitute
x + 8 + 3 x + 2 = 180°
x + 3x + 8 + 2 = 180°
4x + 10° = 180°
4x = 180° - 10°
4x = 170°
x = 170° ÷ 4
x = 42.5
Answer:
They lose about 2.79% in purchasing power.
Step-by-step explanation:
Whenever you're dealing with purchasing power and inflation, you need to carefully define what the reference is for any changes you might be talking about. Here, we take <em>purchasing power at the beginning of the year</em> as the reference. Since we don't know when the 6% year occurred relative to the year in which the saving balance was $200,000, we choose to deal primarily with percentages, rather than dollar amounts.
Each day, the account value is multiplied by (1 + 0.03/365), so at the end of the year the value is multiplied by about
... (1 +0.03/365)^365 ≈ 1.03045326
Something that had a cost of 1 at the beginning of the year will have a cost of 1.06 at the end of the year. A savings account value of 1 at the beginning of the year would purchase one whole item. At the end of the year, the value of the savings account will purchase ...
... 1.03045326 / 1.06 ≈ 0.9721 . . . items
That is, the loss of purchasing power is about ...
... 1 - 0.9721 = 2.79%
_____
If the account value is $200,000 at the beginning of the year in question, then the purchasing power <em>normalized to what it was at the beginning of the year</em> is now $194,425.14, about $5,574.85 less.
<u>Answer</u>:
Given below.
<u>Step-by-step explanation</u>:
1) Hypotenuse
2) Using Pythagoras theorem:
35² + 12² = c²
c = √1225+144
c = √1369
c = 37 ....this is the length of missing side.
Here given that opposite is 35 , adjacent is 12 , hypotenuse is 37.
3) sin(θ) = opposite/hypotenuse
sin(θ) = 35/37
4) cos(θ) = adjacent/ hypotenuse
cos(θ) = 12/37
5) tan(θ) = opposite/adjacent
tan(θ) = 35/12
<u>Given</u><u> </u><u>:</u>
<u>To</u><u> </u><u>Find</u><u> </u><u>:</u>
<u>Answer</u><u> </u><u>:</u>
- x + y = 4 ....[Equation (i)]
- x + y = 1......[Equation (ii)]
<u>Adding</u><u> </u><u>eqⁿ (ii) </u><u>and</u><u> eqⁿ (i) we get :</u>
→ x + y + x - y = 4 + 1
→ 2x = 5
→ x = 5/2
→ x = 2.5
<u>Now</u><u>,</u><u> </u><u>put</u><u> </u><u>the</u><u> </u><u>value </u><u>of</u><u> </u><u>x</u><u> </u><u>=</u><u> </u><u>5</u><u>/</u><u>2</u><u> </u><u>in</u><u> </u><u>eqⁿ</u><u> </u><u>(</u><u>i</u><u>)</u><u> </u><u>we</u><u> </u><u>get</u><u> </u><u>:</u>
→ x + y = 4
→ 5/2 + y = 4
→ y = 4 - 5/2
→ y = 1.5